2008
DOI: 10.1002/ange.200801433
|View full text |Cite
|
Sign up to set email alerts
|

Intergrowth Structure of Zeolite Crystals and Pore Orientation of Individual Subunits Revealed by Electron Backscatter Diffraction/Focused Ion Beam Experiments

Abstract: Das Zwei‐Komponenten‐Modell sargförmiger, verwachsener Kristalle von Zeolith ZSM‐5 wurde mithilfe einer Kombination von Rückstreu‐Elektronenbeugung und Ionenstrahlätzen verifiziert (siehe Bild). Die erste Methode offenbarte die Ausrichtung des Kanalsystems der einzelnen Kristalluntereinheiten, die zweite ermöglichte die Visualisierung dieser Bausteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 34 publications
1
23
0
2
Order By: Relevance
“…The internal architecture of the individual zeolite H-ZSM-5 crystals and the presence of a 908 rotational intergrowth structure has been described in detail in recent publications. [43][44][45][46][47] In the edges, the straight pores are shown to be open to the outer surface, whereas the main body is accessible through the zigzag pore segments. Due to different accessibilities of distinct H-ZSM-5 crystal regions and concurrent pore blockage at the edges of the crystal, as was evidenced for the reaction with styrene derivatives, [12,14] the extent of product formation was found to be different in the edge and the main body.…”
Section: Uv/vis Microspectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The internal architecture of the individual zeolite H-ZSM-5 crystals and the presence of a 908 rotational intergrowth structure has been described in detail in recent publications. [43][44][45][46][47] In the edges, the straight pores are shown to be open to the outer surface, whereas the main body is accessible through the zigzag pore segments. Due to different accessibilities of distinct H-ZSM-5 crystal regions and concurrent pore blockage at the edges of the crystal, as was evidenced for the reaction with styrene derivatives, [12,14] the extent of product formation was found to be different in the edge and the main body.…”
Section: Uv/vis Microspectroscopymentioning
confidence: 99%
“…More details on the crystallographic orientations and concurrent pore alignments of the zeolite H-ZSM-5 crystals under study can be found in recent publications. [43,44] The intense coloration of the zeolite H-ZSM-5 crystals is ascribed to the formation of light absorbing species over the Brønsted acid sites. The dissimilarities in coloration between compounds 1-4 and at different crystal regions are associated with the presence and intensity variations of different UV/Vis absorption bands (Figure 4 b).…”
Section: Uv/vis Microspectroscopymentioning
confidence: 99%
“…On the basis of earlier findings on the oligomerization of styrene derivatives along with the presence of a 908 rotational intergrowth structure, it can be rationalized that the product molecules are aligned and accommodated within the straight pores of the zeolite. [4,27,28,32] Moreover, the continuous presence of the ring vibrations of both reactant and products strongly suggests that a considerable part of the thiophene rings remain intact. Finally, it is important to stress that only in the case of the correct polarization direction, in this case k y, could bands attributed to vibrations of product molecules be visualized.…”
mentioning
confidence: 98%
“…[20] In Figure 1 b, a microphotograph of an individual H-ZSM-5 crystal is presented, along with a schematic representation illustrating the crystals intergrowth structure and crystallographic orientations. [27,28] Within the H-ZSM-5 crystals, which have a two-dimensional pore network with interconnected straight and sinusoidal pores, the direction of the straight pores is parallel to the crystallographic b axis. The nonlinear Raman responses of 2-chlorothiophene as a function of depth within the crystal are presented in Figure 1 c,d for the edge (N) and center (*) regions, respectively.…”
mentioning
confidence: 99%
“…For instance,m ulti-twinning components with pyramidalb oundaries in the ZSM-5 zeolite (FTC: MFI)h ave been uncovered by the electron backscatter diffraction (EBSD) method. [5,6] In the stacking disorder phenomenon, identical buildingl ayers with differents tacking manners along the third dimension are identified. This phenomenon, frequently observedi nt he *BEA, *-ITN, *MRE, *SSO,a nd *STO zeolite families, has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%